2024
DOI: 10.1021/acs.molpharmaceut.3c00845
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of the Pathology and Safety Aspects of Three- and Four-Way Junction RNA Nanoparticles

Kai Jin,
You-Cheng Liao,
Tzu-Chun Cheng
et al.

Abstract: RNA therapeutics has advanced into the third milestone in pharmaceutical drug development, following chemical and protein therapeutics. RNA itself can serve as therapeutics, carriers, regulators, or substrates in drug development. Due to RNA's motile, dynamic, and deformable properties, RNA nanoparticles have demonstrated spontaneous targeting and accumulation in cancer vasculature and fast excretion through the kidney glomerulus to urine to prevent possible interactions with healthy organs. Furthermore, the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 97 publications
0
4
0
Order By: Relevance
“…Subsequent evaluations showcased the nanoparticles’ effectiveness in inhibiting primary tumors as well as lung metastasis of colorectal cancer. The design, quality assessment, and safety evaluation of RNA nanoparticles intended for drug delivery were also evaluated . Two types of RNA nanoparticles were initially designed: a 3WJ scaffold with specific modifications and a 2′F 3WJ scaffold incorporating siRNA targeting survivin.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent evaluations showcased the nanoparticles’ effectiveness in inhibiting primary tumors as well as lung metastasis of colorectal cancer. The design, quality assessment, and safety evaluation of RNA nanoparticles intended for drug delivery were also evaluated . Two types of RNA nanoparticles were initially designed: a 3WJ scaffold with specific modifications and a 2′F 3WJ scaffold incorporating siRNA targeting survivin.…”
Section: Introductionmentioning
confidence: 99%
“…Human genome sequencing has revealed that a majority of nonprotein-coding DNA encodes for noncoding RNAs, marking a paradigm shift that could indicate RNA therapeutics as the third great milestone in pharmaceutical drug development. , The inherent motility and deformability of RNA nanoparticles allow for swift and efficient tumor accumulation through both spontaneous and active targeting, while their negative charge and dynamic nature enable rapid renal excretion for nontumor-accumulated RNA nanoparticles, minimizing potential toxicity concerns. , Additionally, the incorporation of ligands for cancer targeting has further enhanced RNA nanoparticle biodistribution. With properties of self-assembly, programmability, and multivalency, RNA nanoparticles present as a promising material for pharmaceutical applications. These studies explored the application of RNA–drug conjugation to facilitate the controlled release of drugs into their original forms and the utilization of arrow tail RNA for targeted drug delivery to cancer cell cytosols via exosome surface display. , Remarkably, both RNA nanoparticles and RNA-displaying exosomes demonstrated potent anticancer capability, inhibiting cancers and their metastasis efficiently without discernible toxicity. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations